Review on Neural Correlates of Emotion Regulation and Music: Implications for Emotion Dysregulation - Hou, Jiancheng; Song, Bei; Chen, Andrew C. N.; Sun, Changan; Zhou, Jiaxian; Zhu, Haidong; Beauchaine, Theodore P. (Frontiers in Psychology, 2017)
Previous studies have examined the neural correlates of emotion regulation and the neural changes that are evoked by music exposure. However, the link between music and emotion regulation is poorly understood. The objectives of this review are to (1) synthesize what is known about the neural correlates of emotion regulation and music-evoked emotions, and (2) consider the possibility of therapeutic effects of music on emotion dysregulation. Music-evoked emotions can modulate activities in both cortical and subcortical systems, and across cortical-subcortical networks. Functions within these networks are integral to generation and regulation of emotions. Since dysfunction in these networks are observed in numerous psychiatric disorders, a better understanding of neural correlates of music exposure may lead to more systematic and effective use of music therapy in emotion dysregulation.